1997
DOI: 10.1097/00007691-199704000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation and Plasma Clozapine Concentrations in Chinese Patients With Schizophrenia

Abstract: The relationships between clozapine dosages, plasma concentrations, and clinical responses in Chinese schizophrenics were studied. Fourteen treatment-refractory schizophrenic patients were treated with clozapine for 12 weeks. Patients were assessed before and after 6 and 12 weeks of treatment using the Brief Psychiatric Rating Scale (BPRS), the Clinical Global Impression (CGI), and the Simpson-Angus Scale for Extrapyramidal Side Effect. Plasma clozapine concentrations were determined by high-performance liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 15 publications
2
51
2
Order By: Relevance
“…38 In another study, the akathisia scores, as measured by the Simpson-Angus scale, did not significantly improve from baseline in clozapine-treated Asian patients. 39 In contrast, in the present study olanzapinetreated Japanese patients showed significant improvement from baseline (P < 0.001, data not shown) as well as compared to haloperidol-treated patients on the DIEPSS total score and the akathisia item score, while they were on relatively lower doses of olanzapine compared to their Caucasian counterparts. This suggests that olanzapine therapy is associated with fewer EPS compared to the typical agents and perhaps clozapine for Japanese patients with schizophrenia and possibly for other Asian patients with schizophrenia.…”
Section: Discussioncontrasting
confidence: 90%
“…38 In another study, the akathisia scores, as measured by the Simpson-Angus scale, did not significantly improve from baseline in clozapine-treated Asian patients. 39 In contrast, in the present study olanzapinetreated Japanese patients showed significant improvement from baseline (P < 0.001, data not shown) as well as compared to haloperidol-treated patients on the DIEPSS total score and the akathisia item score, while they were on relatively lower doses of olanzapine compared to their Caucasian counterparts. This suggests that olanzapine therapy is associated with fewer EPS compared to the typical agents and perhaps clozapine for Japanese patients with schizophrenia and possibly for other Asian patients with schizophrenia.…”
Section: Discussioncontrasting
confidence: 90%
“…Polymorphisms in the cytochrome P450 2D6 (CYP2D6) gene are a major cause of pharmacokinetic variability in humans, and sufficient evidence suggests ethnic differences in the metabolism of antipsychotics between Asian and western populations [54,55]. For instance, fluoxetine and paroxetine, which are potent CYP2D6 inhibitors, will raise aripiprazole blood levels and thus a lower dose might be used in clinical practice.…”
Section: Clinical Issues In the Use Of Atypical Antipsychotics In CLImentioning
confidence: 99%
“…[22][23] Thus Chinese patients may be more sensitive to rapid clozapine titration, as compared with Caucasians. Clozapine metabolism was also found to be affected by concomitant use of valproate, although the results had been contradicting.…”
Section: The Incidence and Characteristics Of Clozapine-induced Fevermentioning
confidence: 99%